Assessment the Antioxidant and Hypolipidmic Effect of Black Cumin (Nigella sativa L.) Flavonoids in Induced Oxidative Stressed Male Rabbits - Al-Mzaien, Kahtan A. (The Iraqi Journal of Veterinary Medicine, 2012)
Qualitative and quantitative assessment of flavonoids, sugar moiety and antioxidant scavenging activity (in vitro and vivo) of black cumin seed ( Nigella sativa L.) as well as serum lipid profile inhydrogen peroxide (H2O2) induced oxidative stress and flavonoids treated adult male rabbits were the main aim of the current study. The results showed that black cumin seeds contained 4.50gmcrude flavonoids per kg crushed seeds and the high performance liquid chromatography indicated the existence of 22 flavonoids, only seven of which were identified flavonoids represented nearly 2.751gm/kg of the total flavonoids. The concentration of kaempferol was the highest whereas quercetin the lowest. Glucose, fructose and sucrose were the sugar moiety of flavonoids with an average concentration of 3.22, 2.21 and 3.31 g/kg crushed seeds respectively. Assessment the antioxidant scavenging activity of the extracted flavonoids and its effect on lipid profile in H2O2 treated rabbits were carried out as follows; eighteen adult male rabbits were randomly divided into three equal groups. Rabbits in the first group were received tap water and served as control (C), whereas animals in 2nd group received 0.5% H2O2 in drinking tap water (T1), animals in the 3rd group were received 0.5% H2O2 in drinking water with 27.5mg/kg B.W. of black cuminseeds flavonoids.Fasting blood samples were collected at 0, 4, 8 and 12 weeks of the experiment. The results clarified that 0.5% H2O2 in drinking water caused significant elevation in serum malondialdehyde (MDA) and reduction in glutathione (GSH) concentration of treated animals respectively.The incidence of antioxidant scavenging activity in vitro was more pronounced than that recorded in vivo particularly at the early stages of administration and extracted flavonoids ameliorate to a great extent the incidence of hydrogen peroxide induced oxidative stress in male rabbits. The results revealed that administration of 0.5% H2O2 in drinking water for 12 weeks to male rabbits caused significant p<0.05 elevation in TC, TAG, LDL-C and VLDL-C concentration, with significant p<0.05 reduction in serum HDL-C concentration as compared with the control where as Black Cumin seed flavonoids caused significant reduction in the serum concentration of TC, TAG, LDL-C, and VLDL-C and significantly p<0.05 elevation in HDL-C concentration comparing to H2O2 treated group.Conclusion: This study clarified the significant role of black cumin flavonoids in modulation of glutathion (GSH) content and malondialdehyde( MDA) equivalent and exhibited highly hypolipidmic effect.